Lie Algebras In Particle Physics from Isospin To Unified Theories - Georgi, Howard (Taylor & Francis, 2000)
In this book, the author convinces that Sir Arthur Stanley Eddington had things a little bit wrong, as least as far as physics is concerned. He explores the theory of groups and Lie algebras and their representations to use group representations as labor-saving tools.